RISE OF RELIGIOUS VALUES IN THE YEARS OF INDEPENDENCE - Раъно Зокирова (Journals Park Publishing, 2024)
In this article Independence years religious of values rising ways light up given This centuries in the series from the ocean drop -yu, from the sun drop But in Uzbekistan freedom waist from shining since centuries to surprise falling, mind believe who does not big vital there have been changes.
Keywords: Imam al- Maturidi, Burhoniddin al- Marginani, Bahauddin Naqshband, Imam al-Tirmizi, Khoja Ahmad Yassavis independence years, hurriyat waist, vital changes.